Penggunaan Algoritma K-Means Berbasis Website dalam Menentukan Kelompok Pembinaan Al-Qur’an di Pondok Pesantren Islamiyah Syafiiyah Sumberanyar - Rahman, Zainur; Yaqin, Moh Ainol; Syafiih, M (Universitas Nurul Jadid, 2025)
This study aims to develop a web-based application system using the K-Means algorithm to cluster students in Al-Quran training at Pondok Pesantren Islamiyah Syafi’iyah Sumberanyar, Paiton, Probolinggo. The system is designed to improve efficiency and accuracy in determining training groups based on students' Quranic reading skills, including Tajwid, fluency, and memorization. By analyzing data from 824 students, this research successfully classifies them into three skill categories: